Wet bulb and Conilon coffee root distribution under drip irrigation - Souza,Joabe Martins de (2018)
ABSTRACT Knowledge of the wet bulb and the root system of the Conilon coffee plant is highly important for the correct management of irrigation. Therefore, the aim of this work was to characterize the wet bulb and Conilon coffee root distribution under drip irrigation. The experiment was conducted in the city of São Mateus, ES, Brazil with five replications of a completely randomized design of a 4 x 6 split-plot scheme, which represents four points located according to plant location and six depths. Two points were located in the plant line and two points between lines. For row spacing, we used a split-plot scheme 5 x 6 with five points in relation with plant location and six depths with five replications. The coffee roots were analysed by volume, superficial area, length and diameter. The wet bulb was measured with tubes located in six points near the plants with two points in the plant row (between two plants) and five points between rows. The measurements were conducted at four depth ranges with three replications. The wet bulb reached a depth of between 0.40 and 0.50 m, providing an excess of water in depth, evidencing the importance of this characterization for the irrigation management of drip-irrigated Conilon coffee. The depth of the radicular system for better irrigation management efficiency of drip-irrigated coffee is 0.30 m, exhibiting 67.4% of root volume and 68.0% of surface area.